Insider trading in rumored takeover targets. (15th August 2020) - Davis, Frederick; Khadivar, Hamed; Pukthuanthong, Kuntara; Walker, Thomas J.
Abstract: We examine insider trading surrounding takeover rumors in a sample of 1, 642 publicly traded US firms. Using difference‐in‐differences regressions, we find that insider net purchases increase within the year prior to the first publication of a takeover rumor, particularly when rumor articles are either accurate (lead to a takeover announcement) or informative (provide substantial justification for the rumor's publication). Moreover, we find abnormal insider trading to be a significant predictor of takeover announcements occurring within the following year. Finally, passive net purchasing (i.e., selling less rather than buying more) is more pronounced among managing insiders than among non‐managing insiders.